2020
DOI: 10.1038/s41598-020-75012-w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the expression of SLC30A family genes and prognosis in human gastric cancer

Abstract: The solute carrier 30 (SLC30) family genes play a fundamental role in various cancers. However, the diverse expression patterns, prognostic value, and potential mechanism of SLC30A family genes in gastric cancer (GC) remain unknown. Herein, we analyzed the expression and survival data of SLC30A family genes in GC patients using multiple bioinformatic approaches. Expression data of SLC30A family genes for GC patients were extracted from the Cancer Genome Atlas (TCGA) and genetic alteration frequency assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The SLC30 family genes, consisting of 10 members (SLC30A1-10), regulated zinc levels in human cells. Guo et al demonstrated that SLC30 family genes engaged in the regulation of the immune microenvironment in gastric cancer [8]. In particular, SLC30A2 and SLC30A3 may play a pro-metastatic role directly [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SLC30 family genes, consisting of 10 members (SLC30A1-10), regulated zinc levels in human cells. Guo et al demonstrated that SLC30 family genes engaged in the regulation of the immune microenvironment in gastric cancer [8]. In particular, SLC30A2 and SLC30A3 may play a pro-metastatic role directly [8].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al demonstrated that SLC30 family genes engaged in the regulation of the immune microenvironment in gastric cancer [8]. In particular, SLC30A2 and SLC30A3 may play a pro-metastatic role directly [8]. Moreover, Henshall et al showed that the expression of SLC30A4 was elevated in prostate cancer compared to paracancerous tissue and the expression of SLC30A4 in prostate cancer was negatively correlated with the immunoreactivity intensity [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KEGG analysis showed SLC39A family genes to be involved in the hormone regulation, metabolic pathways, mineral absorption, and chemical carcinogenesis pathways ( Ding et al, 2019 ; Zhou et al, 2021 ). Therefore, the prognostic effect of the SLC39A family genes can be speculated to be closely related to zinc transfer, metabolism, and function ( Guo and He, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…An example is that Liu et al [8] generated a prognostic model of autophagy-related genes in nonsmall cell lung cancer. Guo and He [9] analyzed gene expression in the SLC30A family and manifested a likely prognostic marker for gastric cancer. Sui et al [10] generated an immunocyte-related prognosis model that can predict the prognosis of patients effectively and efficacy of chemotherapy by analyzing immunocyte infiltration level in breast cancer.…”
Section: Introductionmentioning
confidence: 99%